The composition and radiolysis impact on aromatic hydrocarbons in sedimentary organic matter from the Mulga Rock (Australia) uranium deposit - Greenwood, Paul F.; Shan, Chao; Holman, Alex I.; Grice, Kliti (Organic geochemistry, 2018)
•Molecular and isotopic distribution of U-rich Mulga Rock sediments reported.•Ionizing radiation effects on aromatic terpenoids were identified.•Radiolysis hastened the diagenetic transformation of plant terpenoids.•The aromatic terpenoid distributions showed no other major radiolytic effects.•Diagenetic products showed a slight 13C enrichment with increasing aromatisation. Our interest in the effect of ionizing radiation on sedimentary organic matter (OM) has extended to the molecular distributions and stable isotopic values of aromatic hydrocarbons. Thermally immature sediments (%Ro = 0.26; Tmax < 421 °C) spanning a 173–5280 ppm radiolytic gradient from the Mulga Rock Uranium Deposit (Western Australia) contained high abundances of vascular plant sourced aromatic (and aliphatic) terpenoids. Terpenoids with 2–5 rings and various levels of aromatisation were detected in the aromatic fractions of these sediments. The extent of aromatisation increased with sedimentary U/radiolytic levels, attributed to free-radical promoted reactions including dehydrogenation and oxidation of aliphatic precursors. The sediment with the highest U content (5280 ppm) showed only diterpenoids and low MW PAHs, reflecting complete radiolytic removal of higher MW terpenoids. A larger number and variety of terpenoid products were detected from the other sediments (U ≤ 1700 ppm) from which several radiolytically promoted reaction pathways were identified. Cadinene, for instance, was subject to competing hydrogenation and dehydrogenation reactions which gave cadinane and progressively aromatised diterpenoid analogues, respectively. Pentacyclic terpane precursors were also progressively aromatised and partially converted to des-A-triterpenoid or C-ring cleaved triterpenoid (tetracyclic) products. These reactions are typical of the natural diagenetic transformation of plant terpenoids, with the main effect of the high radiolytic levels an apparent hastening of diagenetic processes. The δ13C values of several aromatised products indicated a slight 13C enrichment with increasing aromatisation, likely due to preferential abstraction of H from 12C.